2019
DOI: 10.1002/micr.30507
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell‐derived mesenchymal stem cells prolong hind limb survival in a rat vascularized composite allotransplantation model

Abstract: Background The reduction of systemic immunosuppressive agents is essential for the expansion of vascularized composite allotransplantation (VCA) in a clinical setting. The purpose of this study is to compare human‐induced pluripotent stem cell‐derived mesenchymal stem cells (iMSCs) with four other types of mesenchymal stem cells (human bone marrow‐derived MSCs [BMMSCs], human adipose‐derived MSCs [ADMSCs], rat BMMSCs, and rat ADMSCs) in vitro, and to investigate the in vivo immunomodulatory effect of iMSCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…X-SCID rats were utilized to avoid immune rejection by the host; however, the immune systems of these rats are not completely depleted (Mashimo et al, 2010). It is known that human MSCs have immunomodulatory properties (Madrigal et al, 2014), and it has been demonstrated that iMSCs induced from iNCCs also have immunomodulatory properties under xenogeneic conditions (Mitsuzawa et al, 2019). Allogeneic MSC transplantation has been widely used in clinical settings, and HLAediting techniques may provide safety and feasibility in using hiPSCs for allogeneic transplantation (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…X-SCID rats were utilized to avoid immune rejection by the host; however, the immune systems of these rats are not completely depleted (Mashimo et al, 2010). It is known that human MSCs have immunomodulatory properties (Madrigal et al, 2014), and it has been demonstrated that iMSCs induced from iNCCs also have immunomodulatory properties under xenogeneic conditions (Mitsuzawa et al, 2019). Allogeneic MSC transplantation has been widely used in clinical settings, and HLAediting techniques may provide safety and feasibility in using hiPSCs for allogeneic transplantation (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that BM-MSCs may prolong VCA survival through the increased levels of CD4 + CD25 + Tregs, TGF-β1, and serum IL-10 [ 70 ]. A recent study illustrated the induced pluripotent stem cell-derived mesenchymal stem cells (MSCs) also prolonged VCA allograft survival through the induction of T cell hyporesponsiveness, reduction of proinflammatory cytokines (interferon gamma and tumor necrosis factor α), and elevation of the anti-inflammatory cytokine, IL-10 [ 71 ]. AD-MSCs also prolonged VCA allograft survival by suppressing effector T cells and enhancing Tregs [ Table 2 ] [ 72 , 73 ].…”
Section: Mechanism and Outcomementioning
confidence: 99%
“…(2014) [ 81 ] Donor HSCs Swine Fascio-cutaneous 15 × 10 9 (0), IV T cell depletion + non-myeloablatıve TBI + CsA (0–45) Prolong allograft 85–100 days Induce peripheral blood chimerism between 20 and 100% Mitsuzawa et al. (2019) [ 71 ] Syngeneic iMSCs Rat Hindlimb 2 × 10 6 (7), IV Tac (0–6) Prolong allografts >17–21 days Induce T cell donor-specific hyporesponsiveness Kuo et al. (2017) [ 31 ] Autologous AD-MSCs Swine Hindlimb 1 × 10 6 /kg (0–3), IV TBI (−1) + Tac (0–4) Prolong allografts >196 days Modulate T cell regulation Plock et al.…”
Section: Mechanism and Outcomementioning
confidence: 99%
“…iPSC-MSCs also suppressed T-cell effector cells of Th1/Th2 and increased regulatory T cell (Treg) response[ 105 ]. iPSC-MSCs prolonged hind limb survival by reducing mononuclear cell infiltration, lowering TNFα and IFNγ, increasing interleukin 10, and thus protecting against acute rejection in a rat vascularized composite allotransplantation model[ 106 ] (Figure 1 ). iPSC-MSCs disrupted NK cell cytolytic machinery to prevent allograft rejection by decreasing activation markers and ERK1/2 signalling, leading to impaired immunologic synapses and secreted cytotoxic granules.…”
Section: Applications Of Hpsc-mscs In Regenerative Medicinementioning
confidence: 99%